The effectiveness of the trim and fit program in bodyweight management among healthcare providers in Terengganu - Samsury, Siti Fatimah (2024)
Obesity among healthcare providers (HCPs) is a significant concern, impacting both their well-being and patient care quality. This study aims to assess body image perception, the effectiveness of the Trim and Fit Program, and factors associated with successful weight reduction among overweight and obese HCPs in Terengganu. This study started with a cross-sectional study that evaluates body image perception scores and predictors among overweight and obese HCPs. This was followed by a cluster randomized controlled trial to assess the effectiveness of the Trim and Fit Program's impact on weight, body fat percentage, and waist circumference and a cohort study to determine the factors associated with successful weight reduction. The study spanned January to October 2023, involving 201 HCPs with BMI ≥25kg/m2. Participants were selected using a multistage random sampling, with 100 in the intervention group and 101 in the control group. The intervention group underwent a six-month Trim and Fit Program emphasizing nutritional modifications, physical activities, recreational engagement, and motivation. The control group received educational booklets on workplace stress. Data was analysed using multiple linear regression, repeated-measures ANCOVA, and multiple logistic regression (p < 0.05). The mean (SD) scores of body image perception for negative affect, attractiveness, physical functional awareness, and height dissatisfaction are 27.2 (7.78), 18.5 (5.19), 15.7 (3.47), and 8.6 (3.82), respectively. Age and working hours increase with body image satisfaction, while higher BMI decreases with satisfaction. Nursing professionals report increased height dissatisfaction. Higher incomes correlate with better self-evaluation in looks, health, and fitness, while increased education correlates with lower scores. Marriage impacts self-esteem in attractiveness, health, and fitness but increases height satisfaction. The Trim and Fit Program significantly improves body weight, body fat percentage, and waist circumference. Factors associated with successful weight reduction include income, total program attendance, and frequency of calorie intake recording. Body image perception is predicted by sociodemographic and occupational characteristics, but it doesn't significantly contribute to weight reduction success. In conclusion, the body image perception among HCPs in Terengganu highlights the significance of tailored interventions to enhance their self-perception. While the Trim and Fit program has proven successful in improving key health outcomes, the high engagement with the program, particularly through attendance and calorie tracking, is essential for its effectiveness. As a result, resources can now be redirected towards other priorities, recognizing that the program's existing structure effectively achieves its objectives.